Glycaemic, insulinaemic, and immune responses to commercially available beverages consumed during recovery from rowing training - Macdonald, S. L.; Perry, T. L.; Rose, M. C. (European Journal of Sport Science, 2010)
The consumption of carbohydrate and protein after exercise improves muscle glycogen synthesis and attenuates the decrease in immune function seen with endurance-type exercise. However, the impact of consuming commercially available beverages on glycaemic, insulinaemic, and immune responses during recovery from rowing training has not been investigated. Twenty-one male and female rowers completed four trials in a randomized order. Commercially available beverages were consumed in volumes providing 1.2 g carbohydrate · kg-1 body mass, upon completion of ~90 min of rowing at 60-70% maximum oxygen uptake, interspersed with up to five 5-min intervals at or above race pace. Blood samples were taken before and 15, 30, 45, 60, 90, and 120 min after consumption of the beverages for analysis of insulin and glucose and at 90 and 360 min for the analysis of cortisol and interleukin-6 (IL-6). The high-carbohydrate sports beverage and the meal replacement beverage produced a significantly larger (P<0.05) glucose incremental area under the curve than the sports-specific meal replacement beverage or the flavoured milk beverage. The high-carbohydrate sports beverage and the sports-specific meal replacement beverage produced a significantly lower (P<0.05) insulin incremental area under the curve than the meal replacement beverage or the flavoured milk beverage. The meal replacement beverage produced both a high glycaemic and insulinaemic response, suggesting that it may produce a higher rate of muscle glycogen resynthesis. There was a significant interaction between time and beverage for IL-6 (P=0.001), but not for cortisol (P=0.779). These results indicate that the impact of post-exercise nutrition on immune response may not be exclusively mediated by an attenuation of the cortisol response.